Fecal Microbiota Transplantation Is Effective for Postcolectomy Recurrent Clostridioides difficile Infection - Cho, Janice; Roque, Maria Vazquez; Orenstein, Robert; Loftus, Edward V., Jr; DiBaise, John; Pardi, Darrell S.; Khanna, Sahil (Journal of Gastrointestinal Infections, 2022)
Background The outcomes from fecal microbiota transplantation (FMT) for recurrent Clostridioides difficile infection (rCDI) in patients after complete or partial colectomy are not well-defined.Objectives We sought to report our experience with FMT for rCDI in patients who have undergone colectomy.Methods Descriptive analyses of FMT outcomes from 2014 to 2020 were performed in patients who previously had undergone complete or partial colectomy.Results Twenty-nine patients with prior colectomy for inflammatory bowel disease, malignancy, slow-transit constipation refractory to medical therapy, or fulminant CDI underwent FMT for rCDI. Two patients (6.9%) had rCDI within 8 weeks post-FMT. Seven had CDI beyond 8 weeks (median 10 months) with 71% related to antibiotic exposure post-FMT, suggesting a 69% overall success.Conclusion FMT resolves rCDI in most patients after colectomy with subsequent antibiotic exposure predicting CDI after FMT.
Keywords: Clostridioides difficile infection; colectomy; fecal microbiota transplantation